Phage therapy in osteoarticular infections in the era of antibiotic resistance bacteria - Jakub Czarnota; Michał Dobrzyński; Tomasz Wojciech Skubel; Dorota Sokół; Iga Dudek; Małgorzata Drozd; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2020)
The increase in the incidence rate of multidrug resistant strains of bacteria has prompted scientists to look for alternatives to antibiotics. One option is phage therapy. The possibility of using phages (bacteriophages) in infections of almost every organ and system is being investigated. The treatment of osteoarticular infections using antibiotics is often very problematic, which is why this is an important area of interest for phage research. As part of the bacteriophage experimental therapy conducted by Patey et al., 9 patients with osteoarticular diseases were treated. In 7 cases complete recovery was obtained. One patient achieved partial eradication of the pathogen with closure of several fistulas and stabilization of the general condition. The study was carried out on an animal model by Yilmaz et al. showed greater effectiveness in eliminating MRSA colony forming units when combining bacteriophages with antibiotics (drop to 5000 units, no biofilm) than when using antibiotics alone (17,165 units survived, biofilm present). Independent application of phage therapy brought the worst effect (30,788 surviving units). The results of the cited studies indicate the possible effectiveness of phage therapy in the case of osteoarticular infections. The potential synergy of antibiotics and bacteriophages in eradicating bacterial biofilm deserves attention.